2020
DOI: 10.7860/jcdr/2020/45291.14044
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19: How the Radiology Department Should Combat this Global Pandemic

Abstract: The impact of the global pandemic due to novel Coronavirus Disease (nCOVID-19) has been braced by all medical subspecialties, including the radiology department. As Computerised Tomography (CT) of the chest as well as radiographs gain more and more importance in diagnosing, following up and prognosticating this respiratory infection, it becomes essential to have set protocols in place regarding imaging, disinfection and departmental workflow to ensure smooth functioning and protection of patients and health ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It is an innovative approach for detecting lung consolidation and symptoms of viral pneumonia; U.S.fnding out is reportedly robust in shape with chest X-ray and computed tomography (CT) fndings [30,37]. As such, it has miles useful for inspecting the lungs of pregnant girls and youngsters to ofer a radiation-loose point-of-care tool [38]. Te Italian look cautioned a scientifc approach for the overall performance of pulmonary ultrasound tests in pregnant girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an innovative approach for detecting lung consolidation and symptoms of viral pneumonia; U.S.fnding out is reportedly robust in shape with chest X-ray and computed tomography (CT) fndings [30,37]. As such, it has miles useful for inspecting the lungs of pregnant girls and youngsters to ofer a radiation-loose point-of-care tool [38]. Te Italian look cautioned a scientifc approach for the overall performance of pulmonary ultrasound tests in pregnant girls.…”
Section: Discussionmentioning
confidence: 99%
“…After each suspected or infamed patient, deep cleansing ought to be done, with a downtime of about one hour. At some point during the COVID-19 outbreak, air change charges should be multiplied in unique parts of the radiology branch [38].…”
Section: Discussionmentioning
confidence: 99%
“…Few pieces of research are documenting the changes and measures taken regarding education, patient and staff safety, and research within the radiology department. These are mainly published from middle-and high-income countries (8)(9)(10)(11). A study done in a US radiology teaching unit showed that technology integration for distance learning has promise in maintaining the teaching-learning process while applying social distancing.…”
Section: Introductionmentioning
confidence: 99%